Uslūb Reciprocal Teaching wa Istikhdāmuhā Litarqiyyah Mahārah al-Qirā'ah ‘inda al-Ṭalabah bi al-Madrasah Tsānawiyyah Babun Najah - Cut Nurul Ulfa (DAYAH: Journal of Islamic Education, 2020)
The researcher chose this title due to her observation regarding the students at Babun Najah boarding school, that many of them less understanding about the text of Arabic and unable to an understanding about main information in it, and they still lack motivation and board in learning Arabic. Therefore, they need a special method to make them be easy in understanding Arabic texts, namely by using the Reciprocal Teaching model. The aim of this research is to know effectiveness of using the Reciprocal Teaching model to improve students’ ability in understanding Arabic texts. The method of this research is Quasi Experimental. Meanwhile, the population is all students in class XI IA 3 Babun Najah. And while the sample is all students in that class there are 32 students, In order to collect the data, the test (Pre-test and Post-test) was used as an instrument. The study results showed that; 1) The implementation of the Reciprocal Teaching model at Senior High School Babun Najah Banda Aceh was conducted in 4 steps, namely question generating, clarifying, predicting, and summarizing 2) The Use of the Reciprocal Teaching model improved students’ ability in understanding Arabic texts. It was shown by the result of the T-Test 10,5 that is bigger than the result of the Table Test 30,5, it is acceptable.